On a stable solution of the problem of disturbance reduction - Maksimov, Vyacheslav I. (Zielona Góra: Uniwersytet Zielonogórski)
We study the problem of active reduction of the influence of a disturbance on the output of a linear control system. We consider a system of linear differential equations under the action of an unknown disturbance and a control to be formed. Our goal is to design an algorithm for reducing the disturbance by means of an appropriate control on the basis of inaccurate measurements of the system phase coordinates.
Keywords: disturbance reduction; dynamical controlled system; guaranteed control theory